2017
DOI: 10.1177/1403494817716374
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress among Norwegian adolescents: Changes between 2001 and 2009 and associations with leisure time physical activity and screen-based sedentary behaviour

Abstract: The association between physical activity, sedentary behaviour and psychological distress was weak; only high amounts of physical activity and high amounts of screen-based sedentary behaviour were associated with psychological distress. Longitudinal studies are needed to provide further insights into these associations and to understand the extent to which these variables might be causally related.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 25 publications
1
27
2
Order By: Relevance
“…This has also been done in other studies (see e.g. Kleppang, Thurston, Hartz, & Hagquist, 2017). This use of the HSCL-10 to measure mental health problems does not deny that the concept can be, and usually is, interpreted in a wider sense.…”
Section: The Questionnairementioning
confidence: 77%
“…This has also been done in other studies (see e.g. Kleppang, Thurston, Hartz, & Hagquist, 2017). This use of the HSCL-10 to measure mental health problems does not deny that the concept can be, and usually is, interpreted in a wider sense.…”
Section: The Questionnairementioning
confidence: 77%
“…Studies on Norwegian adolescents reported a weak association between PA and mental health problems. Researchers found that only a high amount of PA (at least 11 h per week) was associated with a significantly lower risk of psychological distress [16]. In addition, adolescents who were physically active in a sports club showed a lower level of depressive symptoms compared to those who were inactive [17].…”
Section: Introductionmentioning
confidence: 99%
“…Coping strategies have been suggested to mitigate the effect of stressors [ 8 ]. People with poorer health habits are more likely to have psychological distress [ 9 , 10 , 11 , 12 ]. Interventions promoting healthier lifestyles have been reported to improve mental status [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%